Penerapan Natural Language Processing Untuk Mengidentifikasi Kalimat Ambigu pada Surat Kabar Menerapkan Metode Shift Reduce Parsing - Elya Wita (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Natural Language Processing focuses on the interaction between computers and the natural language used by humans. In other words, the computer process extracts information from input in the form of natural language and / or produces output which is also in the form of natural language.Newspapers are printed sheets containing reports that occur in the community. However, the titles of newspapers often have an ambiguous meaning. When a written or spoken word, phrase, sentence, or even paragraph contains ambiguity, it is automatically ineffective and communicative for the reader or listener. For this reason, it is necessary to identify sentences to make it easier for readers to understand the meaning of an ambiguous title.To make it easier to identify ambiguous sentences in newspapers requires a shift Reduce parsing algorithm, using the Shift Reduce parsing algorithm can be useful to find out what the news writer wants to convey.